Is Fast Feminine?: The Effect of Speed of Observed Hand-Motor Actions on Consumer Judgment and Behaviors - Sayin, Eda; Malik, Sumit (Association of Consumer Research, 2020)
This paper shows that observing a slow (vs. fast) hand-motor action with an advertised product (eg, fabric, shaving foam, etc.) can evince stereotypic feminine (vs. masculine) schematic associations and, subsequently, alter consumer judgment. In three studies, we provide evidence on the effect of dynamic-observed experiences across advertising contexts.
Keywords: Observed Hand-Motor Actions; Schematic Association; Consumer Judgments; 61 Psicología; ODS 5 - Igualdad de género